If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(4c + -2) = 0 Reorder the terms: -2(-2 + 4c) = 0 (-2 * -2 + 4c * -2) = 0 (4 + -8c) = 0 Solving 4 + -8c = 0 Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -8c = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -8c = 0 + -4 -8c = 0 + -4 Combine like terms: 0 + -4 = -4 -8c = -4 Divide each side by '-8'. c = 0.5 Simplifying c = 0.5
| -24+8=m-6 | | 92=-2a-6(a-6) | | 6x+3y=-13+5x+2y | | 8(3x-2y)+4[(-3)+4y]= | | -28+2n=6(n-6) | | 3x=2x+40 | | -4(7+n)=-3n-4(7+4n) | | 21m+11m=340 | | 3x^2+x+12=14 | | -5(-4+3a)= | | 2.8=Z+5 | | 320t=280(t-3) | | 3p-9=4 | | 1x+3x=2a | | 7x-5=3(x-2)+5(1-3x) | | -9x+1.6=-8+1.1 | | p(7p+6)(7p-6)= | | 7x(7x-49)=0 | | -48=8v+8 | | 15=-2n-5n | | 8x^3-1.6x^2+4.1x+3.5=0 | | -20=-5+8(r+9) | | 8*7-4*3+(23)= | | -39-10x=-18x+91 | | 1.5(2.2y+3.4)= | | y+-4=15 | | k-4k=-(k-8)-3(6-k) | | 5=-3t | | 7-x*3=9+5*x | | x(62-x)=961 | | 40+12x=4 | | -0.8x^3-1.6x^2+4.1x+3.5=0 |